2005
DOI: 10.1111/j.1399-302x.2005.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of heat shock proteins but not superantigen by isolated oral bacteria from patients with Behcet's disease

Abstract: We isolated bacteria from periodontal sites and mixed saliva in eight patients with Behcet's disease and surveyed them to determine whether they produced heat shock proteins (HSPs) and superantigen. Cultivable bacterial compositions from periodontal sites and saliva were examined by anaerobic culture using blood agar plates. Gram-negative anaerobic rods such as Prevotella intermedia, Fusobacterium nucleatum, and Capnocytophaga species were predominant in the isolates from the subgingival plaque samples. The St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
(66 reference statements)
2
9
0
Order By: Relevance
“…Kirino et al hypothesized that HSP60 stimulates not only antigen-specific autoimmune responses, but also the innate immune system through constitutively overexpressed TLR4 [73]. These data are consistent with the interpretation that the immune response against TLR4 ligands, such as HSP and LPS, plays an important part in development of BD [76]. By means of western blot analyses, the bacterial composition of the subgingival plaque and saliva collected from patients with BD was investigated and the levels of superantigen and HSP production by the oral bacteria isolated from these patients (groups of S. salivarius and S. mitis as predominant strains, Prevotella spp, Fusobacterium spp) was determined.…”
Section: Heat Shock Proteinssupporting
confidence: 78%
See 2 more Smart Citations
“…Kirino et al hypothesized that HSP60 stimulates not only antigen-specific autoimmune responses, but also the innate immune system through constitutively overexpressed TLR4 [73]. These data are consistent with the interpretation that the immune response against TLR4 ligands, such as HSP and LPS, plays an important part in development of BD [76]. By means of western blot analyses, the bacterial composition of the subgingival plaque and saliva collected from patients with BD was investigated and the levels of superantigen and HSP production by the oral bacteria isolated from these patients (groups of S. salivarius and S. mitis as predominant strains, Prevotella spp, Fusobacterium spp) was determined.…”
Section: Heat Shock Proteinssupporting
confidence: 78%
“…By means of western blot analyses, the bacterial composition of the subgingival plaque and saliva collected from patients with BD was investigated and the levels of superantigen and HSP production by the oral bacteria isolated from these patients (groups of S. salivarius and S. mitis as predominant strains, Prevotella spp, Fusobacterium spp) was determined. The results indicated that the anaerobic strains isolated from the oral cavity of these patients produce HSPs and possibly that HSPs produced by microorganisms in the oral cavity might lead to the acceleration of oral membrane ulceration in patients with BD [76]. Besides their immunodominance as microbial antigens, under various circumstances HSP do elicit immune responses also when (over-)expressed as self antigens by cells or tissues.…”
Section: Heat Shock Proteinsmentioning
confidence: 96%
See 1 more Smart Citation
“…Streptococci are more frequently isolated from the oral cavity of people with BD, who also have more frequent streptococcal infections. Initially, Streptococcus sanguis was the identified strain but others have been isolated [28,29]. We hypothesized that if BD is triggered by a streptococcal infection, anti-neuronal antibodies could mediate some neurological involvement and/or constitute a biomarker to help clinical therapeutic decisions.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that S. sanguinis infection and the sera from patients with BD are both inflammatory stimuli for heterogeneous nuclear ribonucleoprotein. 20 Once again this process refers to molecular mimicry. 13 However, the stimulation of T cells in patients with BD is not specific for this bacteria and is shared with other species, 14 leading to the hypothesis of a non-specific lymphocytic cell hypersensitivity.…”
Section: Behçet's Pathogenesis and Infectionmentioning
confidence: 99%